Solar Radiation Analysis Model and PVsyst Simulation for Photovoltaic System Design - Balo, Figen; Sua, Lutfu S. (wiley, 2018)
Transportation problems of the conventional energy sources bring out the use of renewable energy sources. Environmental issues also play a role in the choice of the use of renewable energy sources. Yet today, rather than environmental requirements, the use of renewable energy has become increasingly important because of strategies used by the developed countries to meet their energy demands. Correspondingly, in recent years, all countries have been working to increase the share of renewable energy among other energy production methods to ensure energy independence. In this study, in order to design photovoltaic (PV) system for maximum efficiency under climatic conditions, solar radiation analysis for a chosen area is conducted. The system is then modeled through the PVsyst simulation software before the PV system is actually set up. Various panels are evaluated in order to determine the ones that are more efficient than the others under the circumstances in which the system is installed. Additionally, by using PVsyst simulation software, information is provided not only about gains and losses of the system but also about system efficiency. The aim of this study is to model a PV system under a set of circumstances and ensure the most appropriate and efficient panel selection under the environmental conditions to achieve results closer to real environment conditions of the PV system through the PVsyst simulation program. This research involves three stages. The solar energy characteristics and potential of a selected region is initially evaluated based on the available data. In the second stage, solar radiation analysis is conducted on Matlab platform using radiation models. Numerous models exist in the literature to calculate the amount of solar radiation reaching any surface on the Earth. Solar radiation models aim to reach solutions taking the conditions of specific regions into consideration. Solar radiation is a significant determinant of the feasibility of solar energy systems to be installed. Due to the lack of meteorological data available for various reasons, a large number of models have been developed to estimate the levels of solar radiation. However, the appropriateness of these models greatly depends on the climatic and environmental characteristics. This is in fact one of the main reasons that increases the number of available models. Finally, the PV system is simulated using PVsyst software. The values of solar radiation in this case are evaluated to be at acceptable efficiency levels to design a photovoltaic system. Although data for a specific case is used here for the purpose of model verification, this study aims to establish a reference for choosing the most efficient solar panel by relying on the solar radiation values obtained for the most efficient photovoltaic system design. The analysis can be further extended to the various cities in existing climatic regions of countries and develop country-wide solar radiation models. © 2019 Scrivener Publishing LLC.
Keywords: data analysis; panel efficiency; Photovoltaic systems; pvsyst simulation; renewable energy; solar energy